Recommendations for the standardization of clinical outcomes used in allergen immunotherapy trials for allergic rhinoconjunctivitis: an EAACI Position Paper. Issue 7 (25th April 2014) - Pfaar, O.; Demoly, P.; Gerth van Wijk, R.; Bonini, S.; Bousquet, J.; Canonica, G. W.; Durham, S. R.; Jacobsen, L.; Malling, H. J.; Mösges, R.; Papadopoulos, N. G.; Rak, S.; et al.
Abstract Background Allergen immunotherapy (AIT) has been thoroughly documented in randomized controlled trials (RCTs). It is the only immune‐modifying and causal treatment available for patients suffering from IgE‐mediated diseases such as allergic rhinoconjunctivitis, allergic asthma and insect sting allergy. However, there is a high degree of clinical and methodological heterogeneity among the endpoints in clinical studies on AIT, for both subcutaneous and sublingual immunotherapy (SCIT and SLIT). At present, there are no commonly accepted standards for defining the optimal outcome parameters to be used for both primary and secondary endpoints. Methods As elaborated by a Task Force (TF) of the European Academy of Allergy and Clinical Immunology (EAACI) Immunotherapy Interest Group, this Position Paper evaluates the currently used outcome parameters in different RCTs and also aims to provide recommendations for the optimal endpoints in future AIT trials for allergic rhinoconjunctivitis. Results Based on a thorough literature review, the TF members have outlined recommendations for nine domains of clinical outcome measures. As the primary outcome, the TF recommends a homogeneous combined symptom and medication score (CSMS) as a simple and standardized method that balances both symptoms and the need for antiallergic medication in an equally weighted manner. All outcomes, grouped into nine domains, are reviewed. Conclusion A standardized and globally harmonized method for analysing the clinical efficacy of AIT products in RCTs is required. The EAACI TF highlights the CSMS as the primary endpoint for future RCTs in AIT for allergic rhinoconjunctivitis.